El desempeño laboral de las secretarias ejecutivas y su incidencia en la atención al usuario del Gobierno Autónomo Descentralizado Municipal en el Cantón Urdaneta de la Provincia de los Ríos. - Núñez Zambrano, Mariana Ninoska (2016)
The present work of the final report, prior to obtaining the Bachelor's degree in Bilingual Executive Secretariat, of the Technical University of Babahoyo, has the purpose of seeking the benefit of the secretaries and users of the Municipal GAD, which aims to determine the incidence Of the work performance of the executive secretaries in the attention to the user of the Autonomous Municipal Government Decentralized of the canton Urdaneta, Province of Los Ríos. And with the following hypotheses: • The labor performance influences in a predominant way in the attention to the public in the Autonomous Government Decentralized Municipal of the canton Urdaneta. • Communication techniques and written expression influence the executive secretaries with the attention to the user of the Autonomous Government Decentralized Municipal of the canton Urdaneta. • Knowledge of the communication tools influence the attention to the user of the Municipal Decentralized Autonomous Government of the canton Urdaneta. • The existence of office equipment with contemporary technology determines the aptitude and attitude of the executive secretaries in the attention to the user of the Autonomous Government Decentralized Municipal of the canton Urdaneta. This allowed me to see the need to suggest a training seminar on the techniques of effective and written communication addressed to the executive secretaries working in the Municipal Autonomous Government (GAD) of the canton Urdaneta which will help to perform better in their Everyday tasks.